Mathematical models for calculating primary numbers: Proposed a teaching criteria for fundamental education (Research, Society and Development, 2021)
In the teaching of mathematics, at the level of Elementary Education, several mathematical contents are developed such as: Integers and Divisibility Criteria, are necessary contents for the development of new mathematical concepts. In this perspective, this research proposed to reflect on the development of calculations to find Sequenced Prime Numbers, based on the proposals of mathematicians Pierre de Fermat, Marin Mersenne and Eratosthenes. Thus, the research aims to propose a mathematical criterion to find Prime Sequenced Numbers in a more practical way for teaching elementary school students. Therefore, a bibliographic survey was carried out through the Google Scholar platform, considering the publication period between 2017-2021, totaling twenty articles, eight books and a monograph, selected due to their relevance to the theme. The results showed that the approach to prime numbers is verified in several thematic axes, such as mathematics and prime numbers, in addition to referring to the complexity in mathematical development for the calculations. After the demonstration of the proposed criterion and its comparison with the models of Fermat, Mersenne and Eratóstenes, it is evident that the proposal fits into a didactic for the mathematics classes, being easy for students to understand, practical and efficient for teaching calculating how to find sequenced prime numbers.